A Self-Triplexing SIW Cavity-Backed Slot Antenna - Kumar, Arvind; Raghavan, Singaravelu (IEEE antennas and wireless propagation letters, 2018)
In this letter, a new design of self-triplexing slot antenna using substrate integrated waveguide (SIW) technique is demonstrated for multiband communication systems. The proposed antenna operates at triple frequency bands (around 6.53, 7.65, and 9.09 GHz) simultaneously utilizing a slot inserted on the top of the SIW cavity and is excited by three separate microstrip lines. By properly optimizing the antenna parameters, an isolation of better than 19 dB is realized between any two input ports, which helps to achieve self-triplexing property. The proposed triplexing antenna preserves simplicity, compactness, and a planar configuration that makes it suitable for highly integrated handheld devices. To demonstrate the significance of the proposed work, the antenna is prototyped, and experimental results show a close agreement with simulations. Moreover, the proposed antenna exhibits the measured gain of 3.1, 4.7, and 3.9 dBi at resonant frequencies with stable radiation patterns.